Demographic influences on Lithuanian physicians’ attitudes toward medical assistance in dying: a cross-sectional study - Bachmetjev, Benedikt; Airapetian, Artur; Jakubauskienė, Marija; Zablockis, Rolandas; Čekanauskaitė, Asta (Frontiers in Psychiatry, 2025)
BackgroundThe topic of end-of-life decisions is important due to aging populations and the rising number of terminal illnesses like cancer. As more people experience suffering, the ethical, medical, and legal debates of these decisions become significant to healthcare policy. Understanding medical professionals’ attitudes is critical for shaping responsible practices and legislation surrounding end-of-life care.MethodsThis cross-sectional study explores the attitudes of Lithuanian physicians toward medical assistance in dying (MAID), including euthanasia and assisted suicide (E/PAS), as well as other end-of-life decisions such as Do-Not-Resuscitate (DNR) orders and Living Wills, including decisions involving patients diagnosed with mental illnesses. A survey of 361 physicians in Lithuanian hospitals was conducted between October 2022 and July 2024, using hospital intranets and on-site distribution to guarantee representative sample. The survey included demographic factors such as age, gender, religious beliefs, and professional experience. Statistical analysis was performed using SPSS version 26.0 and R software. Chi-square tests, Fisher’s exact tests, and logistic regression models were made to determine relationships, with significance set at p < 0.05.ResultsThe analysis showed that 61.2% of physicians supported assisted suicide for terminally ill patients, while only 19.1% supported it for patients with drug-resistant mental illness. Similarly, 61.5% supported euthanasia for terminal illness. Age, religious beliefs, and professional experience were significant determinants of support, with younger and non-religious physicians more likely to endorse E/PAS. Additionally, 92.2% of respondents supported DNR orders with patient consent, though this dropped to 63.1% without patient consent.ConclusionsLithuanian physicians’ attitudes toward E/PAS and other end-of-life decisions are strongly influenced by ethical, religious, and professional considerations. Significantly lower acceptance for psychiatric patients indicates higher sensitivity regarding mental competency and the ethics of E/PAS in such cases. These findings provide important insights for policymakers and healthcare providers in crafting informed and ethical E/PAS guidelines.